PELATIHAN PEMBUATAN DAN PENGGUNAAN PROBIOTIK DALAM BUDIDAYA IKAN AIR TAWAR DI DESA MARGA SAKTI KECAMATAN PADANG JAYA KABUPATEN BENGKULU UTARA - Oktamalia; Rahadian Harry Dewanto; Hety Novitasari; Indra Warman; Parwito Parwito; Edi Susilo (Fakultas Pertanian, 2023)
Marga Sakti Village is a village located in the Padang Jaya District, North Bengkulu Regency, Bengkulu Province. Marga Sakti Village is a Village With the majority of community work dominated by farmers or planters, Marga Sakti Village has various potential natural resource wealth, one of the potentials that can be empowered is freshwater fish farming. In order to increase economic value and reduce the number of unemployment, Marga Sakti Village also has a very strategic role in terms of providing fish resources and freshwater fish productivity land. However, fish farmers in Marga Sakti Village currently still use conventional technology where they do not understand the importance of adding nutrients to feed to speed up the harvest period with optimal results. So far, fish farmers still use traditional technology due to the lack of knowledge and ability of partners so that the obstacles they face are that fish are susceptible to disease, farmed fish often experience a decrease in appetite, poor aquaculture water quality, and slow fish growth rate, thus prolonging the harvest period and increasing production costs. In order to help solve the problems of fish farmers in the village, community service activities were carried out by providing counseling on Training on Making and Using Probiotics in Freshwater Fish Farming in Marga Sakti Village, Padang Jaya District, North Bengkulu Regency as additional nutrients in feed by utilizing cheap, easily available and environmentally friendly ingredients.